Climate Change and Vietnam's Coffee Export Price Dynamics - Dinh Thi Thu , Hong; Nguyen Huu , Tuan; Tran Ngoc , Tho; Tran Thi Hai, Ly; Ho Hoang Gia , Bao (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study examines the impact of Climate change on Vietnam’s Robusta coffee export prices, with Vietnam being the world’s leading Robusta producer and the second-largest coffee exporter. Climate change is measured by deviations in temperature and rainfall from historical averages (1931‒1960). Using monthly data from October 2003 to December 2023, the empirical results from the VAR (Vector Autoregression) model reveal that shocks from rising temperatures and decreasing rainfall drive higher export prices, reflecting how climate change affects the supply-demand balance, increases marginal costs, and ultimately raises export prices. These findings highlight the potential risks that climate change poses to the efficiency of coffee production and exports. They also underscore the importance of developing effective risk management strategies to help stakeholders strengthen resilience and better prepared in an increasingly volatile coffee market.
Keywords: Coffee export prices; Robusta coffee; Climate change; Vietnam